Does the Appearance and Mannerism of Doctors Affect Doctor-Patient Relationship? A Cross-Sectional Study among General Population in Malaysia - Boparai, Delisha Kaur; Ramesh, Keeran; Rajapura, Ama Thathsarani; Gunawardana, Dushan Uvindu; Kyaw, Thin Mon; Soe, Htoo Htoo Kyaw; Moe, Soe; Nadarajah, Nivedita; Htay, Mila Nu Nu (Asian Journal of Public Health and Nursing, 2025)
Background: A strong doctor–patient relationship is crucial for effective diagnosis and treatment. This study aimed to determine the community’s perception toward doctors’ physical appearance, mannerisms, and association with the doctor-patient relationship in Malaysia.  Methods: This cross-sectional study was conducted among the general adult population in Malaysia. Data was collected via an online survey and analyzed using SPSS version 27.  Results: A total of 389 respondents participated in this study. Over half (55.53%) considered professional attire with a white coat is important, and 90.75% preferred doctors to wear name tags. The respondents paid more attention to mannerisms if they were younger age group (18-30 years) rather than the older age group (50 years and above) (Adjusted OR = 4.64, 95%CI: 1.90, 11.36). While the respondents with higher education levels (Postgraduate) were more attentive to mannerisms compared to respondents with SPM – Secondary Education level (Adjusted OR = 6.77, 95%CI: 1.26, 36.53).  Conclusion: The respondents demonstrated increased trust, confidence, and approachability and were more willing to share personal information with doctors dressed in formal attire with a white coat along with name tags. Most respondents felt that both the physical appearance and mannerisms of doctors played a significant role to form a good doctor-patient relationship. Mannerism was considered more important for the doctor-patient relationship among younger aged and higher educated people.